2019
DOI: 10.1515/jpem-2018-0365
|View full text |Cite
|
Sign up to set email alerts
|

A case report and literature review of monoallelic mutation of GHR

Abstract: Background Monoallelic mutations of GHR have been described in idiopathic short stature (ISS), although the significance of these remain unclear. We report a case of ISS with novel monoallelic S219L mutation of GHR and discuss the possible significance of monoallelic GHR mutation in ISS. Case presentation The proband, a 13.9-year-old Japanese boy, had severe short stature (−3.8 standard deviation [SD]). Serum insulin-like growth factor (IGF)-I level and growth hormone (GH) secretion was normal. His parents we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Biallelic variants in the GHR are the most prevalent causes for primary GHI syndrome with classical GHI, phenotypically presenting with severe short stature and prominent insulin-like growth factor (IGF)-1 deficiency. Recently, milder GHI syndrome has been reported to be caused by rare monoallelic GHR mutations that can lead to a dominant-negative effect [ 49 , 59 , 69 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biallelic variants in the GHR are the most prevalent causes for primary GHI syndrome with classical GHI, phenotypically presenting with severe short stature and prominent insulin-like growth factor (IGF)-1 deficiency. Recently, milder GHI syndrome has been reported to be caused by rare monoallelic GHR mutations that can lead to a dominant-negative effect [ 49 , 59 , 69 ].…”
Section: Introductionmentioning
confidence: 99%
“…Today around 100 variants have been identified in the GHR gene that can cause dwarfism in humans, including missense, deletion, nonsense, frameshift and splice site variants. These variants affect signal transduction, ligand binding, and GHR dimerization [ 44 , 49 ]. Studies have shown that recombinant IGF-1 therapy is the only effective treatment and can improve height z-score in LS cases compared to untreated patients, although standard height may not be achieved.…”
Section: Introductionmentioning
confidence: 99%